Effectiveness of a Game-Based Learning Intervention on Premarital Sex Education Knowledge in Rural Adolescents - Ardiansyah, Fino; Melliza, Nur; Ubaidillah, Zaqqi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Free sexual behavior poses significant risks, including sexually transmitted infections, unintended pregnancies, and the potential for illegal abortions. The prevalence of free sexual behavior among adolescents is often attributed to inadequate reproductive health education. This study aims to evaluate the effectiveness of a health promotion program utilizing game-based learning among students in a rural school setting. This study employed a a pre-experimental study pre-post-test group design with a sample of 31 students from Madrasah Tsanawiyah Al-Munawaroh Malang (grade nine). This research did not use a control group. Respondents were provided premarital sex education using power point presentation, a card game and educational BINGO games. Respondents were selected using purposive sampling. Data was analyzed using paired t-test. The game-based learning method demonstrated significant effectiveness in improving adolescents' premarital sex knowledge. The average pre-test knowledge score was 6.0, while the average post-test score increased to 9.6, indicating a substantial improvement. This finding is statistically significant (p = 0.0000.050), suggesting a notable enhancement in cognitive abilities related to premarital sex knowledge among the adolescent participants. Pre-marital sex education delivered through a Game-Based Learning approach, incorporating PowerPoint presentations and games media, has the potential to empower adolescents with the knowledge and skills necessary to establish healthy sexual boundaries, prevent risky sexual behaviors, and reduce the risk of sexually transmitted infections.